Do published patient decision aids for end-of-life care address patients' decision-making needs? A systematic review and critical appraisal. (September 2019) - Phillips, Georgina; Lifford, Kate; Edwards, Adrian; Poolman, Marlise; Joseph-Williams, Natalie
Background: Many decisions are made by patients in their last months of life, creating complex decision-making needs for these individuals. Identifying whether currently existing patient decision aids address the full range of these patient decision-making needs will better inform end-of-life decision support in clinical practice. Aims and design: This systematic review aimed to (a) identify the range of patients' decision-making needs and (b) assess the extent to which patient decision aids address these needs. Data sources: MEDLINE, PsycINFO and CINAHL electronic literature databases were searched (January 1990–January 2017), supplemented by hand-searching strategies. Eligible literature reported patient decision-making needs throughout end-of-life decision-making or were evaluations of patient decision aids. Identified decision aid content was mapped onto and assessed against all patient decision-making needs that were deemed 'addressable'. Results: Twenty-two studies described patient needs, and seven end-of-life patient decision aids were identified. Patient needs were categorised, resulting in 48 'addressable' needs. Mapping needs to patient decision aid content showed that 17 patient needs were insufficiently addressed by current patient decision aids. The most substantial gaps included inconsistent acknowledgement, elicitation and documentation of how patient needs varied individually for the level of information provided, the extent patients wanted to participate in decision-making, and the extent they wanted their families and associated healthcare professionals to participate. Conclusion: Patient decision-making needs are broad and varied. Currently developed patient decision aids are insufficiently addressing patient decision-making needs. Improving future end-of-life patient decision aid content through five key suggestions could improve patient-focused decision-making support at the end of life.